DETECTION OF BETA-2 MICROGLOBULIN GENE AND SOME BIOCHEMICAL PARAMETERS IN WOMEN WITH INFERTILE IN DIYALA PROVINCE (Academicia Globe: Inderscience Research, 2022)
Female infertility is a disorder that occurs in women for many known or unknown reasons. The present study aimed to find out Beta-2 microglobulin gene variants and their association with infertility using conventional PCR and electrophoresis techniques. Furthermore, it showed the differences in some variables such as age, WBC, Hb, Duration of infertility. Forty-five participants were selected for this study, 25 were identified as infertile women, and the rest were considered control (healthy women). Blood samples were collected from the participants on the day (12-13) of the menstrual cycle and sent to the laboratory; all blood samples were preserved. Plasma was isolated from blood cells, ready for immediate DNA extraction, and kept at -20°C. DNA was extracted for detection of the Beta-2 microglobulin gene by PCR. The results of the study are included that higher value of infertile women percentage was (44%) at the age (36-40) year while the lower value of infertile women percentage was (4%) at the age (15-20) year at a level significant (P value0.05). In the end, there are no significant differences between the infertile women group and the control group in WBC count, B2M, Hb, Duration of infertility (year), and Duration of the period (day) at a significant level (p>0.05).